2016
DOI: 10.18805/ijar.8426
|View full text |Cite
|
Sign up to set email alerts
|

First report on in vivo fertility trial of frozen thawed boar semen in India#

Abstract: The present study was conducted to evaluate the in vivo fertility of frozen thawed boar semen. Twenty ejaculates collected from six mature boars were frozen in a programmable freezer. After freezing the semen was evaluated for different sperm quality parameters. Twenty five sows were inseminated artificially utilizing frozen thawed semen. The percentage of sperm motility, live sperm, live intact acrosome, plasma membrane intact sperm, HOST-reacted sperm, live sperm with high mitochondrial membrane potential, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…There was reduction in sperm motility and viability by 20-25% after freezing. In agreement with our results, similar range of postthaw sperm motility and viability were recorded recently (Baishya et al, 2015). Liquid semen maintained significantly (p<0.01) higher sperm motility, viability and plasma membrane integrity from day 0 to 3 as compared to frozenthawed semen (Table 1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…There was reduction in sperm motility and viability by 20-25% after freezing. In agreement with our results, similar range of postthaw sperm motility and viability were recorded recently (Baishya et al, 2015). Liquid semen maintained significantly (p<0.01) higher sperm motility, viability and plasma membrane integrity from day 0 to 3 as compared to frozenthawed semen (Table 1).…”
Section: Resultssupporting
confidence: 92%
“…Recently, Kadirvel et al (2016) also reported that the farrowing rate was significantly superior for semen that used from initial days of preservation as compared to aged semen. The pregnancy rate and farrowing rate recorded in the present study for frozen-semen is in close agreement with Baishya et al (2015) recorded recently, but higher than that reported by Apic et al (2015) and lower than that reported by Didion et al (2011). The study recorded significantly (p<0.01) lower pregnancy rate, farrowing rate and litter size in frozen thawed semen as compared to liquid semen (Table 2).…”
Section: Resultssupporting
confidence: 91%
“…Artificial insemination with chilled sperm is a reproductive biotechnology often used in horse breeding (Olaciregui et al, 2014). However, maintaining the acceptable sperm quality after cooling, which affects the frequency of pregnancy, remains an urgent problem at the present time (Baishya et al, 2015;Pathak et al, 2020;Ugur et al, 2019). The exact reasons for the decreased sperm motility after cryopreservation remain unclear.…”
Section: Introductionmentioning
confidence: 99%